911 eyewitness - Siegel, Richard A.; Blue Star Media Group; Saba Islamic Media ([S.l.] : Richard A. Siegel & Blue Star Media Group ; Kuala Lumpur : Saba Islamic Media (distributor), 2006)
Shows the exposure during tragedy of September 11 by the witness. Also includes the research that has been done about the attack, the building structure and its collapes
Title from title screen
Keywords: September 11 Terrorist Attacks, 2001; Terrorism -- United States